Student attendance system / Mohd Saifulnizam Abu Bakar - Mohd Saifulnizam , Abu Bakar (2004)
Most of the attendance records are still using the old manual filling system or a semi computerized system. This method faced the challenge of keeping its student records up-to-date and accurate and so looked to upgrade their paper-based record systems to an automated one. Realizing the potential and the need of a new system, I have decided to develop this Student Attendance System for lecturer use. The system is a combination of web based and client server architecture application system. Users of this system are able to access this system online. This system is especially developed to meet the need in efficiency of attendance management in FCSIT with a main focus on the lecturers of the faculty. The system is developed using Active Server Pages, Microsoft Access 2000, as well as VBScript and Macromedia Dreamweaver MX.